Bis(2-amino-4-methyl-1,3-thiazole-κN (3))dichloridocadmium(II) - Zhang, Lai-Jun (International Union of Crystallography, 2008)
In the title compound, [CdCl(2)(C(4)H(6)N(2)S)(2)], the Cd(II) atom is coordinated by two chlorido ligands and two N atoms of the 2-amino-5-methyl-1,3-thiazole (amtz) ligands in a slightly distorted tetrahedral coordination geometry. Intra- and intermolecular N—H⋯Cl hydrogen bonding stabilizes the crystal structure. A weak S⋯Cl interaction [3.533 (2) Å] is observed between neighboring molecules.